Byron's doubts: a critical study of Byron's poetry, 1807-24 - Watson, EM (2023)
This thesis offers a literary and critical reading of Byron’s poetry, and a study of his doubts about whether he should have written poetry at all. Despite the energy and variousness of his career as a poet, Byron was often openly irreverent about his art, claiming to have ‘no great esteem for poetical persons’. It is the claim of this thesis that behind that habit of disparagement lay more serious unresolved uncertainties about the value and purpose of poetry. Although Byron’s scepticism is readily acknowledged, extraordinarily little attention has been paid to the quality of his doubt and how it might have affected his creative practice. Yet as this study shows, his doubts were vitally related to his artistry as a poet.